Pengaruh Kepemilikan Kas, Rasio Pengungkit Dan Margin Laba Bersih Terhadap Perataan Laba - Laysa Khamislihi; Annafi Indra Tama (JRAK: Journal of Accounting Research and Computerized Accounting, 2023)
The purpose of this study is to test the effect of cash holdings, leverage ratios and net profit margins with income smoothing. This study uses statistical methods with the type of research that is quantitative. The sampling method in this study is purposive sampling with data sources from the consolidated reports of companies that are included in the manufacturing group in the consumer goods industry. The research period used is from 2017 to 2019. The number of samples used in each period is 24 company samples, so 72 samples are obtained throughout the period in this study. Data analysis was carried out using a logistic regression analysis model and processed with SPSS (Statistical Product and Service Solution) software version 25. The results of this study indicate that Cash Ownership, Leverage Ratio and net profit margin have no effect on Income Smoothing.